2019
DOI: 10.4172/2161-1122.1000535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Periodontal and Hematological Findings in Diabetes Patients- A Case Control Study

Abstract: Background Periodontal disease is a chronic inflammatory disease initiated by bacterial pathogens and modified by various risk factors. Various studies have elucidated the converse side of the relationship between systemic health and oral health proving the adverse effect of systemic health on periodontal disease and vice-versa. Amongst all, a strong correlation has been shown between periodontal disease and diabetes, revealing that periodontitis is a proven sixth complication for diabetes. There is emerging e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…Additionally, absolute differential counts of neutrophils, basophils, lymphocytes and monocytes were increased. This finding is supported by several studies (14, [18][19][20]. However, the Forest plot depicting relative differential WBC count in T2DM.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Additionally, absolute differential counts of neutrophils, basophils, lymphocytes and monocytes were increased. This finding is supported by several studies (14, [18][19][20]. However, the Forest plot depicting relative differential WBC count in T2DM.…”
Section: Discussionsupporting
confidence: 77%
“…Patients with DM are more prone to anemia (16,17). Several studies have revealed that total leukocyte count (TLC), Neutrophil and lymphocyte counts are higher in T2DM patients (14,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%